191k views
3 votes
Solve 3x - 3 =27 - 2x pls answer

User Vtni
by
4.7k points

2 Answers

3 votes

Answer:

x = 6

Explanation:

3x - 3= 27 - 2x

First we put all the x terms to on side, making it 3x + 2x - 3= 27.

Remeber that when we move a term to the other side of the equals sign (=), we change its sign to be the opposite of what it currently is.

Then, we move all the numberics to the other side, so we derieve 3x + 2x = 27 +3. Again, the sign changes when we move it across.

What is left to do is add up the quantities. So 3x + 2x = 5x and 27 +3 = 30.

We are left with 5x = 30. If 5 x's is 30, how much is one? Sinply divide it to get the answer of 30 / 5 which is six!

To make sure the answer is correct substituite 6 in the equation as x and see if its accurate: 3(6) -3 = 7 - 2 (6). And it is!

So x is equal to six.

User Ali Aljarah
by
4.7k points
6 votes

Answer:


\fbox{\begin{minipage}{3em}x = 6\end{minipage}}

Explanation:

Given:

Equation:
3x - 3 = 27 - 2x

Solve for:


x

Solution:

Step 1: Select relevant approach:

Let's move all the components containing x to the left side and other components to the right side (notice the change of sign of each one from + to - or - to +), then calculate
x

Step 2: Perform the calculation:


3x -3 = 27 - 2x

Moving components:

<=>
3x + 2x = 27 + 3

Adding up components:

<=>
5x = 30

Dividing both sides by 5 (coefficient of component containing
x:

<=>
(5)/(5) x = (30)/(5)

Simplifying to work out
x:

<=>
x = 6

Hope this helps!

:)

User WLc
by
5.8k points